Enhancing sustainability: Mix design, mechanical properties and durability of alkali-activated slag-dolomite concrete modified with crumb rubber - Arjun Raj P.K.; Praveen Nagarajan; A.P. Shashikala; Thandiwe Sithole; Blessen Skariah Thomas (Case Studies in Construction Materials)
In the past two decades, geopolymer concrete or GPC was developed as an ecologically friendly substitute to cement concrete, presenting the opportunity to reduce the substantial CO2 emissions linked to cement manufacturing. The present work attempts to evaluate the design of mixes, mechanical qualities, and durability of Ground granulated blast furnace slag-dolomite rubberised geopolymer concrete (GDR-GPC). GGBS and dolomite powder were utilized as binders in geopolymer concrete, with GGBS facilitating ambient curing and dolomite aiding early strength attainment. NaOH and Na2SiO3 solutions were combined and used as the alkalis for the development of GPC. The study involves binary GPC mix design utilising the Taguchi approach to maximize compressive and impact strength. Subsequently, the fine aggregate portion of the optimized GPC is replaced by rubber particles. Crumb rubber (CR), generated through the ambient grinding process of discarded waste tyres, represents a potential source of environmental pollution. It is utilized as a substitution at volume percentages of 5 %, 10 %, 15 %, and 20 % fine aggregates. The performance of the GDR-GPC is analysed according to its workability, dry unit weight, stress-strain behaviour, flexural strength, split tensile strength and impact strength. The formulated sustainable GDR-GPC mixes demonstrate acceptable hardened properties. The compressive strength ranges from 52.14 to 63.58 MPa when crumb rubber replaces fine aggregates in volumetric proportions between 20 % and 5 %. The impact energy and elastic modulus of the GDR-GPC mix with 20 % crumb rubber replacement are 2236 J and 15.41 GPa, respectively. This could create a substantial market for GDR-GPC products in applications that emphasize enhanced impact strength and flexibility, such as impact-resistant barriers and railway sleepers.